Tafsir Ayat Ahkam Tentaang Syar’u Man Qablana dan Kehujahannya Sebagai Dalil Hukum - Imam Yazid (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2017)
Syar‟u man qablana is one of the arguments of Islamic law that disputed its use as a legal proposition. This article explains how the interpretation of verses on syar‟u man qablana and how its endeavor as one of the propositions in Islamic law.  Kata Kunci: Tafsir Ayat, Syar’u man Qablana, Hujah, Dalil Hukum